2020
DOI: 10.2169/internalmedicine.3561-19
|View full text |Cite
|
Sign up to set email alerts
|

Multilocular Cyst of Type 1 Autoimmune Pancreatitis Masquerading as Cancerization of Intraductal Papillary Mucinous Neoplasm

Abstract: A small proportion of intraductal papillary mucinous neoplasms (IPMNs) are accompanied by type 1 autoimmune pancreatitis (AIP); however their clinical courses and image characteristics have not been fully reported. A 65-year-old woman was referred to our hospital for the examination of a pancreatic head cyst that had shown exacerbation for two years. Several images demonstrated a multilocular cyst with a symmetrically thickened, enhanced, cyst wall. Cancerization of IPMN was suspected, and pancreatoduodenectom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…A widespread consensus on AIP image interpretation has now reduced the number of cases with diagnostic difficulty or atypical AIPs; however, a variety of atypical AIPs have been reported. These include a 9 mm, well-demarcated pancreatic mass that was not affecting the main pancreatic duct [57]; a 2 cm mass protruding inside the main pancreatic duct and mimicking a main duct-type intraductal papillary mucinous neoplasm (IPMN) [58,59]; a 3 cm, low-echoic mass concomitant with a branch-type IPMN [60]; a multilocular cyst with progression of symmetric wall thickening during the time course mimicking cancerization of a branch-type IPMN [61]; and a pancreatic mass invading the ascending colon and mimicking invasive pancreatic carcinoma [62]. Many of these lesions were not accurately diagnosed, but some did not undergo unnecessary resection due to a negative workup for malignancies using EUS-FNAB and the sequential confirmation of a steroid response [60,62].…”
Section: Atypical Cases Of Aip and Their Steroid Responsesmentioning
confidence: 99%
“…A widespread consensus on AIP image interpretation has now reduced the number of cases with diagnostic difficulty or atypical AIPs; however, a variety of atypical AIPs have been reported. These include a 9 mm, well-demarcated pancreatic mass that was not affecting the main pancreatic duct [57]; a 2 cm mass protruding inside the main pancreatic duct and mimicking a main duct-type intraductal papillary mucinous neoplasm (IPMN) [58,59]; a 3 cm, low-echoic mass concomitant with a branch-type IPMN [60]; a multilocular cyst with progression of symmetric wall thickening during the time course mimicking cancerization of a branch-type IPMN [61]; and a pancreatic mass invading the ascending colon and mimicking invasive pancreatic carcinoma [62]. Many of these lesions were not accurately diagnosed, but some did not undergo unnecessary resection due to a negative workup for malignancies using EUS-FNAB and the sequential confirmation of a steroid response [60,62].…”
Section: Atypical Cases Of Aip and Their Steroid Responsesmentioning
confidence: 99%
“…Urban land use, by coordinating the relationship between land rent and use, makes reasonable arrangements for industrial land, residential land, and other types of land to meet people's needs. In this paper, we analyze in depth from several angles to improve the efficiency of comprehensive land use and solve the contradiction between not being constrained by land use and meeting the demand for land use, and the result obtained from the overall land use planning is to realize the coordination of environmental, economic, and social benefits [ 4 7 ]. The planning and utilization of urban land resources is no longer a matter of allocating resources at present, but also a matter of coordinating with current urban construction and citizens' working and living standards.…”
Section: Introductionmentioning
confidence: 99%
“…In the current case, a mass appeared at least four years after a macroscopically invisible lesion began causing a retention cyst. The authors' previously-reported AIP case ( 8 ) demonstrated that wall thickening of the multilocular cyst also appeared after two years of follow-up. Umemura et al ( 4 ) described a case of diffuse-type AIP with a long-term follow-up, involving a multilocular cyst without a mass lesion.…”
Section: Discussionmentioning
confidence: 95%
“…Of course, atypical images of pancreatic ductal adenocarcinoma or IPMN (less the mucin-secreting type) could not be denied; however, intraductal neoplasms, such as intraductal tubular neoplasm, intraductal tubulopapillary neoplasm ( 13 , 14 ), and acinar cell carcinoma ( 15 ), were suspected based on the EUS images. Thus far, cases of AIP mimicking malignant IPMN have been reported, showing nodular lesions protruding inside the MPD ( 7 ) or branch duct ( 5 , 9 ), as well as wall thickening around the multilocular cyst ( 8 ). The current case added another image variation of type 1 AIP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation